Does Fe2+ in olivine-based interstellar grains play any role in the formation of H2? Atomistic insights from DFT periodic simulations. Issue 42 (22nd April 2016) - Navarro-Ruiz, J.; Ugliengo, P.; Sodupe, M.; Rimola, A.
Abstract : The presence of Fe 2+ on interstellar silicate surfaces renders them good reservoirs of H atoms that are ready to recombine to form H2 . Abstract : Using periodic DFT-D2 methods, atomistic simulations of interstellar H adsorption and H2 formation on a (010) Fe-containing olivine surface are presented. At variance with the (010) Mg2 SiO4 surface and key to these processes are the large Fe/H interaction energies, suggesting that olivine surfaces are good reservoirs of H atoms for subsequent recombination to form H2 .